Association between weight-adjusted waist index and myopia in adolescents and young adults: results from NHANES 1999–2008 - Xu Han Shi; Li Dong; Rui Heng Zhang; Wen Bin Wei (BMC Ophthalmology, 2024)
Abstract Background Previous studies have indicated a possible link between obesity and myopia, although the results have varied. The objective of this study was to investigate the correlation between a new measure of obesity, the weight-adjusted waist index (WWI), and myopia. Method This cross-sectional study included individuals between the ages of 12 and 25 who participated in a noncycloplegic vision examination as part of the National Health and Nutrition Examination Survey (NHANES) conducted from 1999 to 2008. WWI was calculated as waist circumference divided by the square root of body weight. Myopia was characterized by a spherical equivalent (SE) of ≤ − 0.5 diopters (D) and further categorized into mild (-3.00D < SE≤-0.50 D), moderate (-6.00D < SE ≤-3.00 D), or high (SE≤-6.00 D). We utilized a weighted multivariable logistic regression and a generalized additive model to evaluate the correlation between WWI and myopia. Threshold effects were analyzed, and we performed subgroup analysis and interaction tests. Results A grand total of 11,180 individuals were registered for the study. Decreased myopia severity was observed with higher WWI, as evidenced by elevated SE (β = 0.098, 95% CI: 0.028–0.167). Individuals in the top tertile of WWI experienced a 19.8% decrease in risk compared to those in the lowest group (OR = 0.802, 95% CI: 0.800-0.804; P for trend < 0.001). Similar associations were observed for high myopia. Gender-specific nonlinear associations were found, with different breakpoints for males (10.774) and females (10.025). In males, a significant positive association was found on the right side of the breakpoint (OR = 1.398, 95% CI: 1.038–1.884), while no significant association was found on the left side. Conversely, among females, a negative association was observed on the left side of the breakpoint (OR = 0.679, 95% CI: 0.512–0.899), whereas no notable correlation was detected on the right side. Conclusion Increased WWI level was linked to a lower risk of myopia and high myopia in the overall sample, with gender-specific variations.